Centre of Gravity (C.O.G)-based analysis on the dynamics of the extendable Double-Link Two-Wheeled Mobile Robot - Abdul Rahman, Muhammad Taqiuddin; Ahmad, Salmiah; Akmeliawati, Rini; Altalmas, Tareq, M.; Aula, Abqori (2013)
This paper discusses about the analysis on the centre of gravity (C.O.G) in affecting the input reference of the motion control of the extendable double-link of two-wheeled mobile robot. The proposed system mimics double inverted pendulum, where the angular position of the first link (Link1) is to be varied depends on the value of the angular position of the second link (Link2) and the elongation of the extendable-link (Link3) that is attached to Link2 with different payload. The two-wheeled mobile robot together with the extendable link on Link2 makes that system become more flexible but yet, the system has become more unstable. The inclination of extendable link at any interest angle will affect the C.O.G of the system especially when the payload is having a significant weight. This two-wheeled mobile robot can be balanced on the condition that the system’s center of gravity must be located on the centre of the wheels. Therefore the input reference of Link1 will be determined from the C.O.G analysis of the system with the payload. Preliminary results show that the angular position of Link1 can be set at suitable degree based on C.O.G analysis that is used for motion control.